Hybrid distributed application in banking transaction using remote method invocation - Agus Cahyo Nugroho; Mychael Maoeretz Engel (Universitas Ahmad Dahlan, 2019)
Today banks have many branches in big cities of the world. System usually used a central database in a particular city. Increased of database server performance due to number of users accessing this application should not degrade performance of application. To keep database server performance optimally, application must distributed to the network. In distributed applications it takes a remote method call, that is why we are going to used Remote Method Invocation to develop this system. Based on results of analysis conducted, author can draw following conclusion of the application, which is once the client get a reference from the remote object then method of remote object is called like calling method from local object and methods that we have defined and implemented on remote object can we call or use both on desktop and web applications so we do not need to work twice. This approach makes more effective and efficient in application development, allows for better optimization, eliminates the need for processing of type information at run time and makes a light weight communication protocol possible. We have built a hybrid application, which supports both compile time and run time generation of marshallers in desktop and web application.